Parenting behaviour of mothers, adolescents’ social emotional adjustments and their correlates in intact and non-intact Malay families in Kuala Lumpur - Chiah, Wan Yeng; Baharudin, Rozumah (Universiti Putra Malaysia Press, 2013)
The main objective of the study was to determine the relationship between parenting behaviour of mothers and social emotional adjustments of adolescents in intact and non-intact Malay families. Sample comprised 213 mothers (n = 166 from intact families; 47 from non-intact families), with at least one adolescent child between the ages of 13 and 17 years, and are residing in Kuala Lumpur. The respondents were identified via a name list of the adolescents’ and e-survey. Using a self-administered questionnaire, the respondents provided information on their background characteristics, self-esteem, family functioning, parenting behaviour, and adolescents’ social emotional adjustments. Results revealed that mothers parenting quality and adolescents’ social emotional adjustments in the overall sample were generally moderate. Better parenting behaviour was shown to be positively related to adolescents’ strengths in non-intact family, and negatively related to adolescent’s difficulties in both family types. Additional analysis, however, indicated that family functioning rather than parenting behaviour is a better predictor of adolescents’ social emotional adjustments. Findings imply that parents and families in any structure are important contributors of adolescents’ social emotional adjustments.